Lanthanum zirconate ceramic toughened by ferroelastic domain switching of LaAlO3. Issue 13 (September 2018) - Han, Jing; Wang, Yanfei; Liu, Rongjun; Cao, Yingbin
Abstract: The poor fracture toughness limits the wide application of the cubic lanthanum zirconate (La2 Zr2 O7 ) ceramics. The current study reports a dramatic fracture toughness improvement of lanthanum zirconates by the introduction of lanthanum aluminates (LaAlO3 ), a ferroelastic second phase. A composite ceramic with the composition of x LaAlO3 / (1- x ) La2 Zr2 O7, where x  = 10, 20, 30, 40, 50 mol%, has been fabricated by a spark plasma sintering method. It is found that, the ferroelastic domains of LaAlO3 in x LaAlO3 /(1- x )La2 Zr2 O7 composite ceramics clearly switch towards a direction that is normal to a propagating crack. In addition, the processing zone width of ferroelastic domains is found to decrease with an increase of LaAlO3 inclusion, attributing to that the residual tensile stress in LaAlO3 caused by the thermal expansion coefficient mismatch, which helps to expand the processing zone, decreases with more LaAlO3 included.